"My Dear, Close and Distant Friend" : Nina Berberova's Letters to Sergej Rottenberg (1947-1975) (Kriterium, 2020)
Nina Berberova (1901–1993) almost appears to have lived several lives. First, she was a young writer in the revolutionary Russia. Then she witnessed the hectic 1920s in Berlin and achieved her literary breakthrough in interwar Paris with psychologically finely-honed novels and short stories set in the Russian émigré community. Finally, she went on in the latter half of the century to a career as a Slavist in the United States. She had her eyes on Russia the whole time. As an academic she studied the cracks in the ideological wall and seems early on to have foreseen her return to her homeland. At last, as she approached the age of ninety, she had vanquished the Soviet Union and could go back in triumph in the “revolutionary" year of 1989. In addition to everything else Berberova was an avid letter writer who maintained a great many correspondences. For nearly thirty years she was friends with her Russian – and Petersburgian –countryman Sergej Rittenberg (1899–1975) in Stockholm, to whom she sent more than 150 letters and postcards between 1947 and 1975. A reflection of her thoughts and reading interests, they also provide a glimpse into the genesis of her huge memoir The Italics Are Mine (Kursiv moj). This volume presents Berberova’s letters with an introduction and extensive commentaries by Professor Magnus Ljunggren.